Variation Of Labeling Some Family Of Graph - Tanveera Sultana. H.M, V.J. Sudhakar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this paper, we investigate mean square cordial labeling of Windmill graph and star graph and 1 - Near mean cordial labeling of Helm graph